Analysis on The Graduate Students’ Fossilized Mispronunciation at Pascasarjana Universitas Negeri Makassar - Aryati, Shinta Sutji Rahayu; Muhayyang, Maemuna; Halim, Abdul (ARRUS Journal of Social Sciences and Humanities, 2023)
This article investigated and examined the fossilized mispronunciation on consonant and vowel sounds made by English graduate students in Pascasarjana Universitas Negeri Makassar. This research employed qualitative descriptive design with purposive sampling technique taking Teaching English as a Foreign Language (TEFL) course at Pascasarjana Universitas Negeri Makassar as the subject of this research limited to the students who have an English Bachelor degree as their previous academic background. The data were collected by using classroom observation and interview and analyzed by transcribing the Zoom recording of learning process. The results of this research showed that (1) There were 3 fossilized mispronunciation in vowel sounds (/ə/, /i/, /ɒ/) and 5 fossilized mispronunciation in consonant sounds (/z/, /v/, /θ/, /dʒ/, /tʃ/). Based on these findings, it considers that the fossilization can be avoided by reinforcing the comprehensive input from the lecturers and motivating the students to pay more attention to their pronunciation.